2014
DOI: 10.2337/dc14-0865
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dipeptidyl Peptidase-4 Inhibition on Microvascular Diabetes Complications

Abstract: We performed a review of the literature to determine whether the dipeptidyl peptidase-4 inhibitors (DPP4-I) may have the capability to directly and positively influence diabetic microvascular complications. The literature was scanned to identify experimental and clinical evidence that DPP4-I can ameliorate diabetic microangiopathy. We retrieved articles published between 1 January 1980 and 1 March 2014 in English-language peer-reviewed journals using the following terms: (“diabetes” OR “diabetic”) AND (“retino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(122 citation statements)
references
References 137 publications
2
115
1
3
Order By: Relevance
“…In support of this speculation, several papers have reported the glucose-independent renoprotective effects of DPP-4 inhibition in animal models of diabetic nephropathy. 15,16,18,27 In the present study, we could not clarify the underlying mechanism for the suppression of AGE-RAGE axis in DPP-4-deficient STZ rats. However, it is unlikely that DPP-4 deficiency decreased renal AGEs levels by improving glycemic or lipid parameters because there was no significant difference of these parameters between DPP-4-deficient STZ rats and wild-type STZ rats.…”
Section: Dpp-4 and Age-rage T Matsui Et Alcontrasting
confidence: 38%
See 1 more Smart Citation
“…In support of this speculation, several papers have reported the glucose-independent renoprotective effects of DPP-4 inhibition in animal models of diabetic nephropathy. 15,16,18,27 In the present study, we could not clarify the underlying mechanism for the suppression of AGE-RAGE axis in DPP-4-deficient STZ rats. However, it is unlikely that DPP-4 deficiency decreased renal AGEs levels by improving glycemic or lipid parameters because there was no significant difference of these parameters between DPP-4-deficient STZ rats and wild-type STZ rats.…”
Section: Dpp-4 and Age-rage T Matsui Et Alcontrasting
confidence: 38%
“…[15][16][17] Indeed, linagliptin, an inhibitor of DPP-4, ameliorated kidney fibrosis in type 1 diabetic mice by blocking the endothelial-tomesenchymal transition. 16 Linagliptin administered in addition to stable renin-angiotensin-aldosterone system inhibitors led to a significant reduction in albuminuria in patients with type 2 diabetes and renal dysfunction.…”
mentioning
confidence: 99%
“…Several reports suggest that DPP-4 inhibitors have antiinflammatory effects and can improve bone marrow function [45,46]. The possibility of scission protection by DPP-4 with antiinflammatory agents such as BNP/ANP (brain natriuretic peptide/atrial natriuretic peptide) or NPY (neuropeptide), which are substrates of DPP-4, is suggested, and an intracorporeal inflammation condition is therefore thought to be ameliorated by DPP-4 inhibitor [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that the strict control of the UAE levels is very important. Recently, it was reported that Dpp-4 inhibitors and sodium glucose cotransporter (SGLT)-2 inhibitors decreases albuminuria in patients with DN (17,18). Consequently, the early intervention, example, the use of RAS inhibitors, Dpp-4 inhibitors and/or SGLT-2 inhibitors might be effective for promoting microalbuminuria remission.…”
Section: Discussionmentioning
confidence: 99%